Integrating variable renewables: the benefits of interconnecting thermal and hydropower regions. Issue 3 (5th September 2016) - Tveten, Åsa Grytli; Kirkerud, Jon Gustav; Bolkesjø, Torjus Folsland
Abstract : Purpose: This study aims to investigate the effects of thermal–hydro interconnection on the revenues, market value and curtailment of variable renewable energy (VRE). The increasing market shares of VRE sources in the Northern European power system cause declining revenues for VRE producers, because of the merit-order effect. A sparsely studied flexibility measure for mitigating the drop in the VRE market value is increased interconnection between thermal- and hydropower-dominated regions. Design/methodology/approach: A comprehensive partial equilibrium model with a high spatial and temporal resolution is applied for the analysis. Findings: Model simulation results for 2030 show that thermal–hydro interconnection will cause exchange patterns that to a larger extent follow VRE production patterns, causing significantly reduced VRE curtailment. Wind value factors are found to decrease in the hydropower-dominated regions and increase in thermal power-dominated regions. Because of increased average electricity prices in most regions, the revenues are, however, found to increase for all VRE technologies. By only assuming the planned increases in transmission capacity, total VRE revenues are found to increase by 3.3 per cent and VRE electricity generation increases by 3.7 TWh. Originality/value: The current study is, to the authors' knowledge, the first to analyze the effect of interconnection between thermal- and hydropower-dominated regions on the VRE market value, and the authors conclude that this is a promising flexibility measure for mitigating the value-drop of VRE caused by the merit-order effect. The study results demonstrate the importance of taking the whole power system into consideration when planning future transmission capacity expansions.